EP1012 Giant ovarian mucinous cystadenoma: a case report. (1st November 2019) - Uyanık, E; Özten, G; Orhan, N; Çetiner, S; Gültekin, M; Salman, MC
Abstract : Introduction/Background: Mucinous cystadenoma (MC) is a common benign ovarian neoplasm. The most important feature of a MC is that it can reach much larger sizes than any other adnexial mass. Methodology: In this case report a MC arises from right ovary with a diameter of 40 cm is presented. Results: A 38 year old patient presented with recurrent abdominal pain for 2 months. Physical examination revealed severe abdominal distention and laboratory results showed CA 125 was 152 U/ml. Abdominal tomography revealed a massive cystic mass with no solid component and a diameter of 40 cm (figure 1 ). Midline laparotomy was performed. In exploration, a smooth surfaced mass derived from the right ovary and extending to the bottom of the liver is observed (figure 2 ). Mass was partially adhered to omentum and liver. Salphingoooferectomy was performed. Frozen section was reported as mucinous cystadenoma. Apendectomy was performed. The patient was 72 kilograms before the operation and 57 kilograms in postoperative day 1. Histopathological examination confirmed the diagnosis of benign mucinous cystadenoma. Conclusion: Diferential diagnosis of adnexial masses is difficult due to its extended spectrum and therefore evaluation and management is challenging. Giant ovarian cystadenomas are rarely observed today because of improved imaging techniques. In most cases, USG examination can reveal a complex adnexal mass, however large ovarian cysts require an evaluation of abdomen. As in our case, we performed a CT scan and preoperative evaluation of tumor markers to exclude malignancy. As a conclusion, benign mucinous tumors can reach excessive diameters when neglected and can be a challenge to surgeon. Disclosure: Nothing to disclose.